A 360° GLOBAL PERITONEAL DIALYSIS THERAPY REALITY: CLINICAL EXPERIENCE AND EVIDENCE - Paniagua, Ramón (2021)
Mexico needed to preserve peritoneal dialysis (PD) as a cheaper and accessible treatment without requiring large investments in hemodialysis (HD) facilities. The Mexican Social Security Institute (Spanish: Instituto Mexicano del Seguro Social) (IMSS) facilitated a randomized, multi-center clinical trial, the Adequacy of PD in Mexico (ADEMEX) study, which questioned the use of small molecule clearance to measure PD adequacy and thereby promoted a return to comprehensive clinical evaluation as the most efficient dialysis measure. PD is underutilized in Saudi Arabia and in the Middle East; among the reasons, lack of pre-dialysis education programs and nephrologists expert in catheter insertion, later referral and expansion of outsourcing HD. The King Fahad University Hospital program must be considered one of the most prolific PD centers carrying out clinical studies on the subject. Interest in PD use to manage patients with AKI has been increasing recently. Today there is solid clinical evidence that hypervolemia, hyperpotassemia, acidosis, uremia and hypercatabolism can be well managed by PD in different scenarios. Many of these studies have been performed in a small Brazilian university city, Botucatu. The dilemmas of using PD in aboriginal patients in Australia is discussed here. The focus is on aboriginal people in very remote areas. Some personal views are presented as to the causes of the gap between outcomes for aboriginal and nonaboriginal patients and how the many failed attempts to close the gap could be addressed.